ANALISIS YURIDIS TERHADAP KLAUSULA EKSONERASI PADA PERJANJIAN SEWA MENYEWA SAFE DEPOSIT BOX ANTARA BANK BNI CABANG PEKANBARU DENGAN NASABAH BERDASARKAN ASAS KEBEBASAN BERKONTRAK - Artha Vennessa; Hayatul Ismi; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
A safe deposit box rental agreement is an agreement for the provision of services for storing valuable goods belonging to a tenant which is not prohibited by law in a standard form. The purpose of this Safe Deposit Box rental is to provide tenants with a sense of security from the risk of theft or fire on valuables stored in a safe deposit box. However, in reality the risk of loss, fire, destruction is not covered by the bank as the party providing services as stated in the safe deposit box rental agreement.This type of research can be classified as normative juridical research because this research is conducted by examining secondary data and approaches to legislation. This research examines the principles of law. Sources of data used are primary data, secondary data and tertiary data. The data collection technique used was juridical normative, the data used was literature study.The result of the research conducted by the author is that the responsibility for the loss, damage or change in quality or quantity of SDB storage is entirely borne by the customer. This is not in accordance with the principle of responsibility and consumer protection, where in this lease agreement the bank includes an exoneration clause with the transfer of responsibility. In accordance with the principle of responsibility and article 1365 of the Civil Code, the Bank should provide compensation for losses suffered by customers. Therefore, the government should make laws and regulations regarding agreements, because so far the agreement is still regulated by the Civil Code which is a legacy of the Netherlands and it is necessary to increase customer protection for safe deposit box users in the event of loss of items stored in safe deposit boxes.Keywords: Exoneration Clause, Safe Deposit Box, Responsibility, Consumer Protection Law, Freedom of Contracting Principle.